2017
DOI: 10.1177/1046496417706416
|View full text |Cite
|
Sign up to set email alerts
|

The Intergroup Context of Environmental Education and Approaches to Facilitate Collaboration

Abstract: An exploratory qualitative study examined how collaborations are fostered between newly formed small groups, comprised of individuals holding distinct in-group identities and differing in status. The study context was the environmental education (EE) field known to represent subgroups of educators using unique practices. Participants were environmental educators in a small group in each of three U.S. states, aiming to create inclusive collaborative partnerships. Insights from social identity theory and intergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Collaboration systems that are established with small communities, medium communities, and then large communities will form various changes from small to large scopes that are different from environmental education assistance because the process of representing this sub-group will create change with a better partnership approach without growing social jealousy (Gupta et al, 2017).…”
Section: Figure 4 Al Fajar School Social Service Activitiesmentioning
confidence: 99%
“…Collaboration systems that are established with small communities, medium communities, and then large communities will form various changes from small to large scopes that are different from environmental education assistance because the process of representing this sub-group will create change with a better partnership approach without growing social jealousy (Gupta et al, 2017).…”
Section: Figure 4 Al Fajar School Social Service Activitiesmentioning
confidence: 99%
“…This refers to partnerships that intentionally include individuals and groups who may have historically been excluded or marginalised. These partnerships seek to ensure that all voices are heard and valued and that all parties involved have an equal opportunity to contribute to and benefit from the collaboration (Gupta et al, 2017). This type of partnership is critical in contexts where power dynamics may be unequal, such as between institutions and community groups, or between individuals from different socio-economic backgrounds.…”
Section: Inclusive Collaborative Partnershipsmentioning
confidence: 99%
“…Small groups of programs pursuing EE have been successful when they viewed differences of approach as complementary and beneficial [17,18]. Gupta and colleagues [19] examined two types of collaborations in the USA for incorporating EE in K-12 education: between community groups and between established EE groups. Although both types of collaboration had differences in power balances and EE perspectives, the authors found that awareness among collaborators in both groups about these differences supported more integrated and sustainable group dynamics.…”
Section: Research On Collaboration For Pbeementioning
confidence: 99%